Structural Behaviour and Design of Geopolymer Concrete Members - Prabir Kumar Sarker (Civil Engineering Dimension, 2015)
The worldwide production of concrete is on the increase in order to meet the increasing rate of construction. Since cement production contributes to the greenhouse gas emission, it is vital to develop alternative low-emission binders to reduce the carbon footprint of concrete. Fly ash based geopolymer is an alternative binder that has potential to reduce the CO2 emission of concrete production. It has been shown in different studies that the mechanical properties of geopolymer concrete are comparable to those of ordinary Portland cement (OPC) concrete. This paper describes the behaviour and design aspects of geopolymer concrete structural members. The design aspects presented in this paper are bond of reinforcing steel in pull-out and spliced bars in beams, beams in shear and flexure, and columns in uniaxial and biaxial bending. It is shown that the current provisions for OPC concrete can be conservatively used for design of reinforced geopolymer concrete members.